Training Counsellors to Work with Diverse Populations:An Integrated Approach - Rungta, Susan A.; Margolis, Rhonda L.; Westwood, Marvin J. (Canadian Journal of Counselling and Psychotherapy, 1993)
The counselling literature pertaining to special needs clients describes the problems inherent when counsellors work with clients who are unfamiliar or different from themselves. Increasingly there are demands for additional counsellor training to meet the needs of specific groups such as ethnic or racial minorities, elderly persons, or individuals with disabilities. In this paper a review is presented as a cross-section of strategies developed for training counsellors to work with these populations. It is proposed that these strategies have broader application than the client populations for whom they were initially designed. Training that utilizes these approaches could enable counsellors to develop a foundation from which to work effectively with a wide variety of special populations.